Crack growth behaviour of P92 steel under creep and creep–fatigue conditions. (November 2014) - Shi, K. X.; Lin, F. S.; Wan, H. B.; Wang, Y. F.
<x content-type="archive" xml:space="preserve">Abstract</x> High temperature creep and creep–fatigue crack growth tests were carried out on standard compact specimens machined from ASME P92 steel pipe. The effects of various loading conditions on crack growth behaviours were investigated. Crack initiation time was found to decrease with the increasing initial stress intensity factor under creep condition and further to decrease by the introduction of fatigue condition. For creep test, the crack growth rate can be well characterised by the facture mechanics parameter C*. For creep–fatigue test, the crack growth behaviour is dominated by the cycle dependent fatigue process when the hold time is shorter, but it becomes dominated by the time dependent creep process when the hold time becomes longer.